Evaluation of Future Anxiety Levels and Specialization Motivation of 4th and 5th Year Students of Dentistry Faculty - Bilge, Kübra; İpek, İrem (Harran Üniversitesi, 2025)
Aim: This study aimed to assess the levels of future-related anxiety and the motivations for specialization among 4th and 5th year dental students at Fırat University Faculty of Dentistry. Material and Methods: A cross-sectional survey was administered to 143 dental students using a 20-item structured questionnaire. The survey included items addressing demographics, perceived adequacy of dental education, concerns about post-graduation employment, and intentions regarding the Dental Specialty Examination (DSE). Data were analyzed using IBM SPSS Statistics 23.0, with chi-square tests employed for categorical comparisons (p < 0.05). Results: A majority of students (66.4%) expressed concern about securing employment after graduation, and 57.3% found their undergraduate education insufficient. Furthermore, 74.1% reported feeling unprepared for the DSE. Despite these concerns, 76.2% intended to take the exam, driven mainly by professional development (35%) and financial incentives (27.3%). Conclusion: The results indicate substantial levels of future-related anxiety among dental students, primarily stemming from perceived inadequacies in clinical training and uncertainty about career prospects. These findings highlight the need to strengthen dental education and provide academic and psychosocial support to better prepare students for professional challenges.
Keywords: Dentistry (Other); Diş Hekimliği (Diğer)